Business terminology in negotiation = Thuật ngữ kinh tế trong đàm phán Thương mại Quốc tế - Đỗ, Mai Anh (2021)
Nowadays, with the development of globalization and economic integration, economics and the related issues have become one of the most-mentioned topics worldwide. Therefore, the need for a good command of English is more and more increasing. It is vital for people, especially students majoring in Economics and businessmen, to have deep understandings of English for economics in general as well as business terminology in particular. By employing 30 English business negotiation conversations, the study demonstrates the understandings of the dominant part in business that is negotiation, as well as how language is used in terms of terminology. The result confirms the exploitation of terminology in negotiation conversations. Nevertheless, the syntactic and sematic features of business terms are also revealed. Finally, some classifications are given with the hope to enhance the knowledge of terminology so that people could communicate with one another better.